Inland Port in Malaysia: Logistical Revisit - Mohd Saifudin, Adam; Zainuddin, Nizamuddin (Springer Nature Singapore Pte Ltd, 2021)
Malaysia inland ports play a significant role in the freight transport system providing access for manufacturers and producers in the hinterland to seaports, as gateways to the nation’s trade. The current Malaysia inland ports in services include Padang Besar, Ipoh, Nilai, Segamat and Tebedu to facilitate containers’ movements to major seaports (i.e., Port Klang, Penang Port and Port of Tanjung Pelepas) and goods across the borders (Tebedu). This chapter’s objective is to review the logistical importance of inland ports in Malaysia. As for that matter, this chapter had collected various experiences of developing inland ports, reviewed their facilities and functions, and highlighting their importance. The findings suggest that an inland port in the northern region of peninsular Malaysia is logistically relevant for an intermodal transportation hub in the Northern Corridor Economic Region (NCER), and a vital hub in line with the One Belt One Road (OBOR) initiative.